Rater reliability and scoring duration of the Quality Function Measure in ambulant children with hyperkinetic movement disorders. (17th February 2016) - Tustin, Kylee; Gimeno, Hortensia; Morton, Erin; Marsden, Jonathan
Abstract : Aim: To examine intra‐ and interrater reliability/agreement, and time taken to score, when the Quality Function Measure (QFM) is applied to children with hyperkinetic movement disorders (HMD; e.g. dystonia, chorea, athetosis, tremor, and myoclonus). Method: Fifteen ambulant children with HMD participated (eight males, seven females; mean age 13y 7mo, SD 3y 7mo). Three trained raters (two physiotherapists, one occupational therapist) independently scored the QFM using videos of each child performing Gross Motor Function Measure (GMFM) Stand and Walk/Run/Jump dimensions. Reliability was evaluated using intraclass correlation coefficient (ICC) model 2.1, Standard Error of Measurement (SEM), and Bland–Altman methods. Results: Rater reliability was excellent for all five QFM attributes: intrarater ICCs ≥0.98 (95% confidence interval [CI] 0.83–1.00), and interrater ICCs ≥0.96 (95% CI 0.91–1.00). SEM varied from 2.07% to 4.72% points for intra‐ and interrater scores across QFM attributes. Bland–Altman tests demonstrated close agreement between ratings, with absolute mean differences varying from 0.34% to 3.23% (intrarater) to 1.67% to 3.82% (interrater). Median scoring duration time was 83 minutes (range 56–144min, SD 16.02). Interpretation: Low measurement error attributable to rater effects suggests the QFM has potential as an evaluative measure in research studies involving children with HMD, though its lengthy scoring requirements are an important consideration for clinical practice. Evaluation of test–retest reliability and responsiveness is required. What this paper adds: Criterion‐trained raters can reliably use the Quality Function Measure (QFM) in children with hyperkinetic movement disorders. The low measurement error related to rater effects supports the QFM as a potential evaluative measure. The QFM may be more viable in a research setting given its lengthy scoring requirements. This article is commented on by Wright on pages789–790 of this issue.